The Mannheim Enterprise Panel (MUP) and firm statistics for Germany - Johannes Bersch; Sandra Gottschalk; Bettina Müller; Michaela Niefert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The Mannheim Enterprise Panel (Mannheimer Unternehmenspanel - MUP) of the Centre for European Economic Research (ZEW) is the most comprehensive micro database of companies in Germany outside the official business register (which is not accessible to the public). The MUP is based on the firm data pool of Creditreform e.V., which is the largest credit rating agency in Germany. At the end of 2013, the MUP contained information on 7.7 Mio firms, of which about 3.2 Mio were still active. Comparisons of the active stock of firms in the MUP with the Business Register of the Federal Statistical Office indicate that the MUP gives by and large a representative picture of the corporate landscape in Germany. The MUP is a valuable database for analyzing the number of start-ups and firm closures on a yearly basis for Germany. Further, the MUP is the sampling frame for the ZEW firm surveys and it is used for analyzing the development of firms over time.
Keywords: C8; L26; 330; firm data; start-ups; firm closures; stock of firms in Germany